2009
DOI: 10.1177/1558689809334210
|View full text |Cite
|
Sign up to set email alerts
|

On Quantitizing

Abstract: Quantitizing, commonly understood to refer to the numerical translation, transformation, or conversion of qualitative data, has become a staple of mixed methods research. Typically glossed are the foundational assumptions, judgments, and compromises involved in converting disparate data sets into each other and whether such conversions advance inquiry. Among these assumptions are that qualitative and quantitative data constitute two kinds of data, that quantitizing constitutes a unidirectional process essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
475
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(492 citation statements)
references
References 30 publications
(32 reference statements)
3
475
0
14
Order By: Relevance
“…This procedure was adopted in order to add clarification, facilitate pattern recognition and extract meaning from data 26 . The variables generated by this process were grouped as "viewpoints" and organized in the domains "infrastructure and service organization" of the PHCPS and "dispensing practices and medicine availability".…”
Section: Resultsmentioning
confidence: 99%
“…This procedure was adopted in order to add clarification, facilitate pattern recognition and extract meaning from data 26 . The variables generated by this process were grouped as "viewpoints" and organized in the domains "infrastructure and service organization" of the PHCPS and "dispensing practices and medicine availability".…”
Section: Resultsmentioning
confidence: 99%
“…All data were entered into the NVivo (2008) software program for data management. The data were quantified to reduce them in a manner to optimize descriptive, interpretive, and internal validity (Maxwell, 1992;Sandelowski et al, 2009), and they focused on the range of experiences of reported benefits. Three members of the research team sorted statements that were similar into distinct categories.…”
Section: Resultsmentioning
confidence: 99%
“…Although this process of quantification has been criticized because of its significant losses of variance (Sandelowski, 2009), we considered it appropriate to summarize the data analyzed by means of the normative and narrative content analysis.…”
Section: Resultsmentioning
confidence: 99%